Integrate the use of fundamental and technical analysis on the transport and logistics sector stocks in the Singapore exchange (SGX) - Tan, Nelson Say Hoe (2018)
Throughout the history, many investors and traders try to profit from the stock market by using a variety of techniques. While some like to rely heavily on technical analysis, others like rely on fundamental analysis of the company. Fundamental and Technical analysis are two of the most common techniques use in stock investment or trading. The project is aim to integrate both the techniques and identify the best transport and logistics stock in the Singapore Stock Exchange(SGX). The quantitative data were collected from Bloomberg terminal and StockFacts from SGX. Metastock Program is used to study the technical aspect of the Stocks.